A Novel Metaheuristic for Travelling Salesman Problem. (18th July 2013) - Zharfi, Vahid; Mirzazadeh, Abolfazl
Abstract : One of the well-known combinatorial optimization problems is travelling salesman problem (TSP). This problem is in the fields of logistics, transportation, and distribution. TSP is among the NP-hard problems, and many different metaheuristics are used to solve this problem in an acceptable time especially when the number of cities is high. In this paper, a new meta-heuristic is proposed to solve TSP which is based on new insight into network routing problems.